‘Begin met moed onder Gods zegen’: Strategieën van verzuiling bij de paters-Norbertijnen 1890-1940 - Sengers, Erik (Religie & Samenleving, 2019)
The pillarization of Dutch society is a much-studied phenomenon. Generally, four theories explain the rise of this societal constellation: emancipation of religious minorities, protection of religious minorities, modernization and mobilization, and pacification of minorities’ interests. This paper evaluates these four theories with the case of the social activists of Berne Abbey. This abbey is part of the Norbertine order and between 1890 and 1940, it hosted four priests who were deeply engaged in the social question, particularly concerning farmers, small entrepreneurs and employers. They founded and organized catholic professional organizations and cooperations for members, and ultimately contributed to catholic corporative society in the Netherlands. The conclusion is that before 1906-1916 – when bishops ordered exclusively catholic organizations – emancipation thesis is valid, but after that period the protection thesis. Also: for members modernization thesis can explain the case, but for leaders in the movement, social pacification was an important motivation. The pillar was not a monolith, and originated in reaction to external and internal tensions.